KOMITMEN DAN PEMBERIAN REWARD TERHADAP EFEKTIVITAS PEMBELAJARAN BINTARA MAHASISWA POLTEKAD DENGAN MEDIASI MOTIVASI BELAJAR - Triyono, Joko; Hadiyati, Ernani; Hadiati, Sri (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract: The purpose of this study was to determine the effect ofcommitment and rewards on the effectiveness of learning mediatedby learning motivation at the NCO Students of Army Polytechnic.Based on the data analysis by path analysis, the independentvariable that has the strongest influence on Learning Effectiveness(Y) is Commitment (X1) which is equal to 0.293. Towards LearningEffectiveness through Learning Motivation (Z), Commitment (X1) alsohas a stronger influence than the Reward (X2) of 0.2211. So that theCommitment variable (X1) is the variable that most influences theLearning Effectiveness (Y) both directly and through intermediariesLearning Motivation (Z). While the variable Rewarding (X2) has asmaller effect on Learning Effectiveness (Y) both directly and throughthe intermediaries of Learning Motivation (Z).Keywords: Commitment, Giving Reward, Learning Motivation,Learning Effectiveness